Hydrogen-bond-induced quantum interference in single-molecule junctions of regioisomers. Issue 33 (9th August 2022) - Ge, Lingbing; Hou, Songjun; Chen, Yaorong; Wu, Qingqing; Long, Lanxin; Yang, Xingzhou; Ji, Yu; Lin, Luchun; Xue, Guodong; Liu, Junyang; Liu, Xiaodong; Lambert, Colin J.; et al.
Abstract : We demonstrate that the effect of solvent–molecule interaction through hydrogen bonding on junction conductance depends on whether transport through the junction is controlled by destructive or constructive quantum interference. Abstract : Solvents can play a significant role in tuning the electrical conductance of single-molecule junctions. In this respect, protic solvents offer the potential to form hydrogen bonds with molecular backbones and induce electrostatic gating via their dipole moments. Here we demonstrate that the effect of hydrogen bond formation on conductance depends on whether transport through the junction is controlled by destructive quantum interference (DQI) or constructive quantum interference (CQI). Furthermore, we show that a protic solvent can be used to switch the conductance of single-molecule junctions between the two forms of quantum interference. To explore this possibility, two regioisomers (BIT-Zwitterion and BIT-Neutral ) were synthesized and their single-molecule conductances in aprotic and protic solvents were investigated using a scanning-tunneling-microscope-based break junction technique, combined with density functional theory and quantum transport theory. We find that the protic solvent twists the geometry of BIT-Zwitterion by introducing intermolecular hydrogen bonds between the solvent and target molecule. Moreover, it increases the energy gap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the molecule by imposing different electrostatic gating on the delocalized HOMO and localized LUMO, leading to a lower conductance compared to that in aprotic solvent. In contrast, the conductance of BIT-Neutral increases due to a transformation from DQI to CQI originating from a change from a planar to a folded conformation in the protic solvent. In addition, the stacking between the two folded moieties produces an extra through-space transport path, which further contributes to conductance. This study demonstrates that combinations of protic solvents and regioisomers present a versatile route to controlling quantum interference and therefore single-molecule conductance, by enabling control of hydrogen bond formation, electrostatic gating and through-space transport.